1995
DOI: 10.1093/carcin/16.10.2523
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of dietary 4-ipomeanol on DNA adduct formation by the food mutagen 2-amino-3-methylimidazo [4,5-f]quinoline (IQ)in male CDF1 mice

Abstract: The food mutagen 2-amino-3-methylimidazo[4,5-f]quinoline (IQ) is carcinogenic in the CDF1 mouse liver, lungs and stomach. IQ is activated to its ultimate carcinogenic form by N-hydroxylation, catalyzed principally by hepatic microsomal cytochrome P450IA2, and further esterification, resulting in the formation of N-(deoxyguanosin-8-yl)-IQ and other adducts. The furanoterpenoid 4-ipomeanol (IPO) is a naturally occurring pneumotoxin which exerts its specific toxicity in Clara cells of the lung after activation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…With one exception (256), the dietary concentrations of the inhibitors listed in Table III were not toxic to the animals. In certain organs, or with certain protocols, however, both CHL and I3C may act as tumor promoters (257,(259)(260)(261).…”
Section: Inhibition Of Aia-dna Adduct Formation and Chemoprevention Omentioning
confidence: 93%
See 1 more Smart Citation
“…With one exception (256), the dietary concentrations of the inhibitors listed in Table III were not toxic to the animals. In certain organs, or with certain protocols, however, both CHL and I3C may act as tumor promoters (257,(259)(260)(261).…”
Section: Inhibition Of Aia-dna Adduct Formation and Chemoprevention Omentioning
confidence: 93%
“…In in vivo studies in rodents, a number of agents have been shown to inhibit AIA-DNA adduct formation in various organs, usually including the target organ (Table III) (242)(243)(244)(245)(246)(247)(248)(249)(250)(251)(252)(253)(254)(255)(256). The dietary agents studied most widely include CHL, conjugated linoleic acid (CLA) and indole-3-carbinol (I3C) (242)(243)(244)(245)(246)(247).…”
Section: Inhibition Of Aia-dna Adduct Formation and Chemoprevention Omentioning
confidence: 99%
“…I3C was purchased from Sigma Chemical Company (St. Louis, MO). Materials for the 32 P-postlabeling assay were obtained from the same sources as before [32]. Powdered AIN-76A diet was prepared in the laboratory as described before [33], except that the antioxidants were omitted.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…7,12-Dimethyl(a)anthracene hydroxylation (Gentil and Sims, 1971), benzo(a)pyrene hydroxylation (Hietanen and Vainio, 1973;Wiebel et al, 1973), phenobarbital-inducible coumarin dealkylation (Lehrmann et al, 1973), aniline and biphenyl hydroxylations, and ethylmorphine N-demethylation (Chhabra et al, 1974) were all attributed to P450 activity in mouse enterocytes. Later studies identified P450 expression more specifically in mouse enterocytes: CYP1A1 was identified following its induction by BNF (Torronen et al, 1994) and by a polychlorinated biphenyl mixture, but only in Ah receptor-positive mice (Cummings and Schut, 1995); CYP3A was detected in mouse small intestine by erythromycin and cyclosporine activities and by immunoblot analysis (Berg-Candolfi et al, 1996); CYP1A, CYP2B, CYP2C, and CYP3A proteins were demonstrated to be induced in mouse small intestine by a food contaminant, imazalil (Muto et al, 1997); and CYP24 mRNA was induced in mouse small intestine by 1,25-dihydroxyvitamin D3 (Yoshimura et al, 1998). In one recent report, antibodies to rat CYP1A, 2C, 2D, 2E1, and 3A were used to probe P450 protein expression in the small intestine of untreated mice.…”
Section: Rat and Mouse Small Intestinal P450 Expressionmentioning
confidence: 99%